Computerized sociometric assessment for preschool children. (July 2015) - Endedijk, Hinke M.; Cillessen, Antonius H. N.
In preschool classes, sociometric peer ratings are used to measure children's peer relationships. The current study examined a computerized version of preschool sociometric ratings. The psychometric properties were compared of computerized sociometric ratings and traditional peer ratings for preschoolers. The distributions, inter-item correlations, and reliabilities of sociometric scores were comparable between the computerized assessment and traditional assessment. The computerized assessment provided additional data for further analysis of the peer evaluation process. Therefore, computerized peer ratings are a promising tool for sociometric measurement with preschool children.